Efficacy and safety of selective TYK2 inhibitor, deucravacitinib, in a phase II trial in psoriatic arthritis. Issue 6 (3rd March 2022) - Mease, Philip J; Deodhar, Atul A; van der Heijde, Désirée; Behrens, Frank; Kivitz, Alan J; Neal, Jeffrey; Kim, Jonghyeon; Singhal, Shalabh; Nowak, Miroslawa; Banerjee, Subhashis
Abstract : Objective: To evaluate the efficacy and safety of an oral selective tyrosine kinase 2 (TYK2) inhibitor, deucravacitinib, in patients with active psoriatic arthritis (PsA). Methods: In this double-blind, phase II trial, 203 patients with PsA were randomised 1:1:1 to placebo, deucravacitinib 6 mg once a day or 12 mg once a day. The primary endpoint was American College of Rheumatology-20 (ACR-20) response at week 16. Results: ACR-20 response was significantly higher with deucravacitinib 6 mg once a day (52.9%, p=0.0134) and 12 mg once a day (62.7%, p = 0.0004) versus placebo (31.8%) at week 16. Both deucravacitinib doses resulted in significant improvements versus placebo (p≤0.05) in the multiplicity-controlled secondary endpoints of change from baseline in Health Assessment Questionnaire-Disability Index and Short Form-36 Physical Component Summary score and in Psoriasis Area and Severity Index-75 response. Improvements were also seen in multiple exploratory endpoints with deucravacitinib treatment. The most common adverse events (AEs) (≥5%) in deucravacitinib-treated patients were nasopharyngitis, upper respiratory tract infection, sinusitis, bronchitis, rash, headache and diarrhoea. There were no serious AEs and no occurrence of herpes zoster, opportunistic infections and major adverse cardiovascular events, or differences versus placebo in mean changes in laboratory parameters with deucravacitinib treatment. Conclusions: Treatment with the selective TYK2 inhibitor deucravacitinib was well tolerated and resulted in greater improvements than placebo in ACR-20, multiplicity-controlled secondary endpoints and other exploratory efficacy measures in patients with PsA. Larger trials over longer periods of time with deucravacitinib are warranted to confirm its safety profile and benefits in PsA. Trial registration number: NCT03881059 .